Physiotherapy practice patterns for patients undergoing surgery for lung cancer: a survey of hospitals in Australia and New Zealand - Cavalheri de Oliveira, Vinicius; Jenkins, Susan; Hill, Kylie (Blackwell Publishing, 2013)
Background: There has been a recent increase in the research available to guide physiotherapy management of patients who require surgical resection for lung cancer. It is unclear whether this evidence has influenced clinical practice. Aim: To describe physiotherapy practice patterns in the preoperative and postoperative management of patients who undergo surgical resection for lung cancer. Methods: Physiotherapists involved in the management of patients who require surgical resection for lung cancer at hospitals across Australia and New Zealand were mailed a purpose-designed questionnaire. Results: The response rate was 91% (43/47). Prior to surgery, 40% (n = 17) of the respondents indicated that patients were not assessed by a physiotherapist. In most hospitals (n = 39; 91%), patients did not participate in supervised exercise training before surgery. Most commonly, physiotherapy was commenced on the day following surgery (n = 39; 91%), with walking-based exercise being the treatment that was most frequently implemented in all patients (n = 40; 93%). Seventy-two per cent of respondents referred less than 25% of patients to pulmonary rehabilitation on discharge from hospital. Physiotherapy assessment and treatment choices were influenced predominantly by established practice in the hospital and personal experience rather than research findings. Conclusion: In people who undergo surgical resection for lung cancer, physiotherapy services focused on reducing or preventing postoperative pulmonary complications. Despite recent data suggesting that exercise training is beneficial in this population, our data indicate that referral to pulmonary rehabilitation was uncommon.